The Silk Road, Bitcoins and the Global Prohibition Regime on the International Trade in Illicit Drugs: Can this Storm Be Weathered? - Raeesi, Reza (Glendon Journal of International Studies, 2015)
This paper examines the effects of the Silk Road on the global prohibition regime on the international trade in illicit drugs. Situating the FBI’s effort in shutting down the online illicit drugs black market, it is argued that The Silk Road represents a fundamental challenge to this global prohibition regime. The paper will look at how this challenge is shaped through the technological difficulties the complexities of The Silk Road has dealt law enforcement agencies and legislative bodies looking to regulate and expand this prohibition regime in the virtual world. It is also argued that the approach taken by law enforcement efforts in this regard is problematic and doomed to fail. Lastly, this paper looks at controlled samples of social media reactions to gage public response to this phenomenon in order to explain the lack of clear moral opprobrium against this type of criminal activity. Cet essai examine les effets de la plateforme Silk Road sur le régime de prohibition globale du commerce international de drogues illicites. Localisant les efforts du FBI visant à fermer le marché noir en ligne de drogues, on reconnaît que Silk Road représente un défi fondamental au régime de prohibition globale. Cet essai explore ensuite les manières dont la technologie a façonné les tactiques et stratégies utilisées par les organismes d’application dela loi et les organes législatifs cherchant à réguler et à combattre ce monde illicite virtuel. Plus spécifiquement, on illustre la problématique de l’approche transparaissant des efforts d’application de la loi à cet égard, argumentant ainsi qu’elle soit vouée à l’échec. Enfin, cet essai analyse des échantillons contrôlés des réactions sur les médias sociaux afin de mesurer la réponse du public à ce phénomène et d’expliquer le manque d’opprobre moral clair contrece type d’activité criminelle.